2022
DOI: 10.1371/journal.pone.0276529
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided tissue acquisition for splenic lesions: A systematic review and meta-analysis of diagnostic test accuracy

Abstract: Background and aims At present, it is difficult and risky to diagnose splenic lesions by conventional needle biopsy using computed tomography (CT) or ultrasound (US). Endoscopic ultrasound (EUS)-guided tissue acquisition is increasingly being used as a new technique to determine the tissue diagnosis of splenic lesions. Therefore, our goal was to determine the efficacy and safety of EUS-guided tissue acquisition for splenic lesions. Methods We performed a systematic review and meta-analysis to evaluate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, the use of EUS in tissue acquisition for the diagnosis of splenic lesions has increased during recent years. In a recent systematic review and meta-analysis, the authors reported an EUS-guided tissue acquisition diagnostic specificity of 77% and sensitivity of 85%, with no major complications [ 78 ]. In another meta-analysis, Lisotti et al demonstrated a diagnostic accuracy of 93% and overall accuracy of 88% for tissue acquisition using EUS-FNA in all the articles reviewed.…”
Section: Upper Gastrointestinal (Gi) Tractmentioning
confidence: 99%
“…Therefore, the use of EUS in tissue acquisition for the diagnosis of splenic lesions has increased during recent years. In a recent systematic review and meta-analysis, the authors reported an EUS-guided tissue acquisition diagnostic specificity of 77% and sensitivity of 85%, with no major complications [ 78 ]. In another meta-analysis, Lisotti et al demonstrated a diagnostic accuracy of 93% and overall accuracy of 88% for tissue acquisition using EUS-FNA in all the articles reviewed.…”
Section: Upper Gastrointestinal (Gi) Tractmentioning
confidence: 99%